Evaluation of analgesic and anti-inflammatory activity of a combination of tramadol-ibuprofen in experimental animals - Chidambarann Suthakaran; Muniyagounder K Kayalvizhi; Karnam Nithya; Thozhudalangudy AR Raja (Wolters Kluwer Medknow Publications, 2017)
Background: Pain is the major concern of patients attending dental clinics, and satisfactory pain relief has always been difficult to achieve. Since the pathophysiology of pain is a complex, central and peripheral nervous system process, combined analgesic regimens with different mechanisms of action as a multimodal approach are becoming popular among the clinicians and dentists. Objectives: The aim of the present study was to evaluate the analgesic and anti-inflammatory activity of ibuprofen and tramadol when used alone or in combination in animal models of pain and inflammation. Animals and Methods: The animals were divided into six groups with six animals in each group. Analgesic activity was assessed by hot plate method in rats and by acetic acid-induced writhing test in mice. Paw edema model in rats after induction with 0.1 mL of 1% carrageenan was used to assess the anti-inflammatory activity. Statistical Analysis: Analysis of variance followed by Tukey's honestly significant difference post hoc test was used for statistical analysis. Results and Conclusion: Combined use of tramadol and ibuprofen provided enhanced analgesic and anti-inflammatory effects in animal models of pain and inflammation.